5.7k views
2 votes
Solve for x -x2+3x+4=0

Solve for x -x2+3x+4=0-example-1

2 Answers

2 votes

So for this, I will be factoring by grouping. Firstly, what two terms have a product of -4x² and a sum of 3x? That would be -x and 4x. Replace 3x with -x + 4x:


-x^2-x+4x+4=0

Next, factor -x² - x and 4x + 4 separately. Make sure that they have the same quantity inside of the parentheses:


-x(x+1)+4(x+1)=0

Now you can rewrite the equation as
(-x+4)(x+1)=0

Now, apply the Zero Product Property to solve for x as such:


-x+4=0\\-x=-4\\x=4\\\\x+1=0\\x=-1

Your final answer is D. x = -1 and x = 4.

User Mattia
by
5.9k points
6 votes

The correct answer is D) x = 4 and x = -1

In order to solve this, we plug into the quadratic equation.

x =
\frac{-b +/- \sqrt{b^(2) - 4ac } }{2a}

In this case, a is the coefficient of x^2 (-1), b is the coefficient of x (3) and c is the constant (4). Now we plug in and solve.

x =
\frac{-(3) +/- \sqrt{3^(2) - 4(-1)(4) } }{2(-1)}

x =
(-3 +/- √(9 + 16 ) )/(-2)

x =
(-3 +/- √(25 ) )/(-2)

x =
\frac{-3 +/- 5 } }{-2}

And then we'll split into the two possible answers.

(-3 + -5)/-2 = -8/-2 = 4

(-3 - -5)/-2 = 2/-2 = -1

User Erayerdem
by
5.7k points